Harnessing the potential of big data in post pandemic Southeast Asia. - Thompson, Fraser; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Digitalization has gained more prominence amid COVID-19 and has highlighted the value of big data for public sector management. The brief explains the potential benefits of big data for public services such as health, social protection, and education and how this can contribute to the post pandemic recovery. It also assesses the key enablers and policy actions needed to realize big data benefits in the region.
Keywords: Information technology -- Southeast Asia; Economics; Electronic book